Chromosomal localization of the human c-fms oncogene. - Groffen, J (1983)
A molecular probe was prepared with specificity for the human cellular homologue of transforming sequences represented within the McDonough strain of feline sarcoma virus (v-fms). By analysis of a series of mouse-human somatic cell hybrids containing variable complements of human chromosomes it was possible to assign this human oncogene, designated c-fms, to chromosome 5. Regional localization of c-fms to band q34 on chromosome 5 was accomplished by analysis of Chinese hamster-human cell hybrids containing as their only human components, terminal and interstitial deleted forms of chromosome 5. The localization of c-fms to chromosome 5 (q34) is of interest in view of reports of a specific, apparently interstitial, deletion involving approximately two thirds of the q arm of chromosome 5 in acute myelogenous leukemia cells.